Recyclable Hypersensitive Fluorescent Dipeptidyl Chemosensor Based on Silica Nanoparticles Using Signal Amplification for the Detection of Hg(II) and Cu(II) in Aqueous Solutions. (11th March 2015) - Han, Songyi; Jung, Kwan Ho; Neupane, Lok Nath; Thirupathi, Ponnaboina; Lee, Keun‐Hyeung
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10204-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>